INCREASING CHLOROPHYLL CONTENT AND YIELD OF EGGPLANT ON VARIOUS MAGNESIUM DOSES - Dewi HS, Endang Sri; Tanari, Yulinda; Pangli, Marten; Toyip, Toyip (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2025)
Eggplant is a vegetable that is rich in vitamin and antioxidant so is beneficial for health. Base on this, demand for eggplant continues to increasing. Eggplant production can be increased by increasing the chlorophyll content with additional doses of magnesium (Mg). Mg is the main component of chlorophyll and plays an important role in various plant metabolic pathways. Puprpose of this study determine effect of Mg on increasing Chlorophyll content and its correlation with increasing eggplant yields. This research was conducted in August-Desember 2023 in the Integrated Garden Rumah Tani Nusantara located in Kayamanya Village, Poso. Central Sulawesi. This Study was designed in CRBD, treatment with 6 levels of Mg doses, namely without Mg doses as control. 0.5 g.polybag-1, 1 g.polybag-1, 1.5 g.polybag-1, 2 g.polybag-1, 2.5 g.polybag-1 with three replications. The parameters observed were chlorophyll content ( chlorophyll a, b and Total), plant height and yield component (number of fruits, fruit weight and Fruit Length). The results showed that the Mg dose treatment increased the chlorophyll content of eggplant leaves, both chlorophyll a, b, plant height and yield components. There is a correlation between increased eggplant yields and magnesium doses.